High-density transposon libraries utilising outward-oriented promoters identify mechanisms of action and resistance to antimicrobials. Issue 22 (13th November 2020) - Coward, Chris; Dharmalingham, Gopujara; Abdulle, Omar; Avis, Tim; Beisken, Stephan; Breidenstein, Elena; Carli, Natasha; Figueiredo, Luis; Jones, David; Khan, Nawaz; Malara, Sara; Martins, Joana; et al.
ABSTRACT: The use of bacterial transposon mutant libraries in phenotypic screens is a well-established technique for determining which genes are essential or advantageous for growth in conditions of interest. Standard, inactivating, transposon libraries cannot give direct information about genes whose over-expression gives a selective advantage. We report the development of a system wherein outward-oriented promoters are included in mini-transposons, generation of transposon mutant libraries in Escherichia coli and Pseudomonas aeruginosa and their use to probe genes important for growth under selection with the antimicrobial fosfomycin, and a recently-developed leucyl-tRNA synthase inhibitor. In addition to the identification of known mechanisms of action and resistance, we identify the carbon–phosphorous lyase complex as a potential resistance liability for fosfomycin in E. coli and P. aeruginosa . The use of this technology can facilitate the development of novel mechanism-of-action antimicrobials that are urgently required to combat the increasing threat worldwide from antimicrobial-resistant pathogenic bacteria. Abstract : The authors develop a mutagenesis procedure for use in the identification of antimicrobial mechanisms of action and resistance and identify a potential resistance mechanism for fosfomycin.